2021
DOI: 10.22495/jgrv10i1art1
|View full text |Cite
|
Sign up to set email alerts
|

Different types of government and governance in the blockchain

Abstract: This research work, a study was carried out on blockchain technology and its types, as well as the creation of new models of government and governance from the scope of an organization, infrastructure and platform. Governance and commercial models were addressed, based on standardization of data and legal frameworks. On the other hand, it showed how operational governance causes consequences in business models, whether with transactions, multi-signature, forks, consensus mechanism, smart contracts, tokenizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Current research has not established a link between government regulation and firm self-regulation (Covarrubias and Covarrubias, 2021). The primary contribution of this research, thus, is in showing that information-based regulation can result in firm self-regulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Current research has not established a link between government regulation and firm self-regulation (Covarrubias and Covarrubias, 2021). The primary contribution of this research, thus, is in showing that information-based regulation can result in firm self-regulation.…”
Section: Discussionmentioning
confidence: 99%
“…, 2018). Existing research has found little or no association between government policies and firm self-regulation (Covarrubias and Covarrubias, 2021; Demirel and Kaido, 2011; Christmann and Taylor, 2006; Demirel et al. , 2018).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Evidently, public DLTs such as Bitcoin lack a proper governance structure. Nevertheless, developers and community involved in this DLTs can control and make compatible technical changes with the approval of the majority nodes (Llamas Covarrubias & Llamas Covarrubias, 2021). Mostly permissioned protocols are deployed by extended enterprise to govern their DLTs implemented.…”
Section: Governance Actors and Categories Of Dlts In Extended Enterpr...mentioning
confidence: 99%
“…DLT governance mechanisms is an important element as supports operational governance of how DLT will work (Llamas Covarrubias & Llamas Covarrubias, 2021). DLT governance consensus mechanisms radically lessen bureaucracy that can occur with the DLT network (John & Pam, 2018).…”
Section: Governance Consensus Mechanism For Dlt Deployment In Extende...mentioning
confidence: 99%